KINERJA KARYAWAN PUBLIC AREA SECTION PADA HOUSEKEEPING DEPARTMENT DI EMERALD GARDEN HOTEL INTERNATIONAL MEDAN - Iramaharani Hutabarat; Andi Moh Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Public Area section employee is a shield of a hotel who isn  directly confronted with guest services and comfort regarding cleanliness. This study aims to determine how the employee’s performance and determine the factors that affect the performance of the employees of the public area section at the Emerald Garden Hotel International Medan. Using qualitative descriptive methods,researchers interviewed from 5 respondents. While the data collection techniques in this study used observation,interviews and documentation. Based on the results of research that has been done that so far the employee’s performance is quite good despite having several things that affect the performance of the employee. As for these factors namely personal factors,leadership factors,team factors,system factors and situational factors.Keywords : employee performance,public area section,factors .